Sustainability of Rural Tourism and Promotion of Local Development - Antonietta Ivona (MDPI, 2021)
This Special Issue contains articles include, but not limited to, empirical, analytical, or design-oriented approaches to the following topics: Monitoring of carrying capacity and mechanisms for managing tourist flows in rural areas; Systems and tools to measure the social, economic, and environmental sustainability of rural tourism; Integration between public tourism policies and private strategies in the promotion and implementation of sustainable practices; Policies for promoting public participation in the planning and development of sustainable rural tourism; The impacts of tourism on traditional agricultural activities; Identity enhancement of the territory and its productions; "Good practices" in the implementation of rural tourism sustainability
Keywords: 300; rural revitalization; rural tourism; heritage preservation; cinema; filmic discourses; rural areas; landscapes; gendered interpretation; territorial identity; Camino de Santiago; sustainability; landscape; brand equity; organic agriculture; peripheral areas; local development; heritagisation; sustainable rural tourism; stakeholders; disaffected citizens; sustainable development; Triple Bottom Line; rural development; agriculture; sustainability matrix; cultural ecosystem services; ecosystem; Nemunas Delta; Curonian Lagoon; permaculture; downshifting; development; local resources; marginal areas; National Strategy for Inner Areas (SNAI; Strategia Nazionale per le Aree Interne); sustainable local development; experiential tourism; Romania; case study; territorial valorization; rural hospitality services; Transylvania; sport; tourism; “ borgo” tourism development; rural area; sustainable tourism; periurban; multifunctional agriculture; periurban parks; n/a